Genetic Diversity of Zooxanthellae from Several Host in the Coral Reef Waters at Bokor Island Jepara - Purnomo, Pujiono Wahyu (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
In the life history of coral, which is almost no corals living without zooxanthellae. Some clade of zooxanthellae have been identified and found. Studies on clade of zooxanthellae contributes to the diversity of the information andexplanations which provides for the meaning of the phenomenon of fluctuations in coral reefs, include at around coral reef waters of Bokor Island Jepara. This study aims to evaluate the diversity of zooxanthellae derived from several types of hosts and distribution of its existence. Research was conducted at the Brackishwater Aquaculture Development Centre (BBPBAP) Jepara between July to October 2005. Provision of zooxanthellae has been done with the stage ofpurification, whereas for the evaluate of zooxanthellae diversity by using DNA analysis with RFLP (RestrictionFragment Length Polymorphisme) technique and continued with the phylogenik analysis to perform grouping among clade found. Results showed that : (a) Variation of zooxanthellae clade diversity from host sea anemone, tridacna, Acropora, Favites and Goniastrea are clade A, clade B and clade C, with the zooxanthellae clade Tridacna and sea anemones profile by 80% are clade A and 20% are clade B; zooxanthellae clade profile from Acropora by clade A (60%), clade B (20%) dan clade C (20%); zooxanthellae clade profile from Favites by clade A (20%), and clade C (80%) and zooxanthellae clade profile from Goniastrea by clade A (60%), and clade C (40%). (b) Based on the distribution of the host, then clade A is predominantly found in shallow depths (<3m). Key words: Zooxanthellae, clade